Association of HLA‐A, ‐B, ‐C, ‐DRB1 and ‐DQB1 alleles at amino acid level in individuals with schizophrenia: A study from South India. (22nd July 2020) - Seshasubramanian, Vani; Raghavan, Vijaya; SathishKannan, Aruna Devi; Naganathan, Chandramouleeswaran; Ramachandran, Aparna; Arasu, Priya; Rajendren, Preeti; John, Sujit; Mowry, Brian; Rangaswamy, Thara; Narayan, Saranya; Periathiruvadi, Srinivasan
Abstract: Background: Schizophrenia, a chronic severe psychiatric illness of unknown aetiology, has been shown to be associated with HLA alleles but at varied degree in different population. The present study has focussed on analysing the frequency of HLA class I and class II alleles in persons with schizophrenia from South India. Methods: Ninety seven individuals with schizophrenia and 103 age‐ and gender‐matched controls were typed for HLA‐ A, B, C, DRB1 and DQB1 loci by next‐generation sequencing in Illumina MiniSeq using MIA FORA NGS FLEX HLA typing kit. Results: The results showed that HLA‐A*01:01:01, B*37:01:01 and C*01:02:01 were positively associated with schizophrenia while HLA‐B*35:03:01 and DRB1*04:03:01 were negatively associated. Gender‐specific associations revealed that DRB1*10:01:01 and DQB1*05:01:01 were positively associated while DQB1*03:02:01 was negatively associated with female subjects with schizophrenia. A*24:02:01~B*37:01:01~C*06:02:01~DRB1*10:01:01~DQB1*05:01:01 is the predominant haplotype in schizophrenia population when compared to healthy controls. Amino acid association in susceptible and protective alleles has shown that the presence of peptide in the peptide‐binding groves of mature HLA‐A protein (K, M, V, R and V at 44th, 67th, 150th, 156th and 158th position), HLA‐B protein (D and S at 77th and 99th position) and HLA‐C protein (M at 99th position) confer susceptibility to the disease, only in the absence of E (Glutamic acid) at 74th position in mature HLA‐DRB1 protein. Interaction of amino acids in protective alleles namely B*35:01:01 and DRB1*04:03:01 has revealed that aspartic acid at 114th (D) position in mature HLA‐B protein and glutamic acid (E) at 74th position of mature HLA‐DRB1 protein have a combined effect in protecting against the disease. Conclusion: The study has revealed the HLA association with schizophrenia in south Indian population. The amino acid interaction with the disease needs to be confirmed in a larger population.